1991
DOI: 10.1001/archsurg.1991.01410320088012
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Focused Ultrasound in the Treatment of Experimental Liver Cancer

Abstract: High-intensity focused ultrasound (HIFU) was used to treat Morris rat hepatoma 3924A implanted in the liver. Treatment was administered with a lens-focused 4-MHz transducer that created a focused beam of 550 W/cm2 at peak intensity. One hundred twelve rats with liver tumors were divided into two groups of 56 each. Group 1 received HIFU therapy while group 2 (the control group) did not. All rats were killed immediately or 1, 3, 7, 14, 21, or 28 days after treatment. Eight rats in each group were killed at each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(77 citation statements)
references
References 26 publications
1
75
0
1
Order By: Relevance
“…HIFU treats inner tumor without damaging outside body. Previous research on animal angiography indicated that after treating liver tumor of Morris rat using HIFU, nourishing blood vessels which diameter was less than 200 µm of irradiation zone closed, but they were normal for blood vessels which diameter was more than 200 µm [15] . Secondly, accuracy.…”
Section: Discussionmentioning
confidence: 96%
“…HIFU treats inner tumor without damaging outside body. Previous research on animal angiography indicated that after treating liver tumor of Morris rat using HIFU, nourishing blood vessels which diameter was less than 200 µm of irradiation zone closed, but they were normal for blood vessels which diameter was more than 200 µm [15] . Secondly, accuracy.…”
Section: Discussionmentioning
confidence: 96%
“…The mechanism mentioned to explain the synergy between the two treatments is based on the increase in intracellular penetration of the chemotherapy, thanks to the direct and indirect effects of HIFU: the direct effect concerns the area treated by HIFU (75% of the tumoral volume) where there is an increase in blood flow and in the permeability of the tumor cell membrane thus facilitating the supply and intracellular penetration of docetaxel. 8 The cavitation generated by HIFU takes place with creating a circulating fluid flow ('microstreaming') in the interstitial tissue exposed and inducing shear forces who can created gaps between endothelial cells. 11,19 The indirect effect that concerns the nontreated tumoral area (25% of the tumoral volume) might be related to the regional hyperthermia caused by the HIFU and the diffusion of the ultrasound beam.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that tumor cells were more sensitive to hyperthermia (from 41.5 to 43.51C) than normal cells. 8 Moreover, hyperthermia and docetaxel have a common action since hyperthermia itself favors the disorganization of the microtubular system. 20 In the group 3, chemotherapy was administered 24 h before HIFU treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations